Effects of High-Intensity Aerobic Exercise on Cardiovascular Disease Risk Factors and Inflammatory Markers in Normal Weight Obese Women Aged 20-30 - Jae-Myun Ko; Wi-Young So; Sung-Eun Park (The Asian Journal of Kinesiology)
OBJECTIVES This study aimed to evaluate the effects of high-intensity aerobic exercise on cardiovascular disease risk factors and inflammatory markers in normal weight obese women aged 20–30 years. METHODS Participants were divided into a high-intensity aerobic exercise group (HIEG, n=8) and a control group (CG, n=7). The aerobic exercise protocol was set at an intensity of 80-85% of the maximum oxygen uptake (VO2max), which was determined through an exercise tolerance test, and consisted of a treadmill workout three times a week over a period of eight weeks. To assess the effects of the exercise intervention, the pre- and post-intervention body composition and VO2max were measured. Additionally, blood samples were collected to analyze cardiovascular disease markers and inflammatory cytokines. RESULTS The results indicated that the HIEG group experienced a significant reduction in body weight and fat percentage (p<0.001) along with an increase in VO2max (p<0.001) compared to the control group. Furthermore, the levels of total cholesterol, low-density lipoprotein cholesterol and triglycerides showed a significant reduction (p<0.01) and inflammatory markers such as tumor necrosis factor-α (TNF-α) and high sensitivity C-reactive protein (hs-CRP) were significantly decreased in the HIEG group (p<0.001). Moreover, high-density lipoprotein cholesterol levels were significantly elevated in the HIEG group (p<0.001). CONCLUSIONS These findings suggest that eight weeks of high-intensity aerobic exercise is effective in improving body composition and promoting positive changes in markers for cardiovascular disease and inflammation in normal weight obese women.